Didática da história e EJA: investigações da consciência histórica de alunos jovens e adultos - Barbosa, Aline do Carmo Costa (2013)
This research has as its central objective to investigate the historical consciousness of students enrolled in the basic EJA (Education of Younths and Adults) of the Colegio Estadual Visconde de Mauá, in the city of Goiânia. The debates regarding the definition of historical consciousness are placed in the field of History Didadicts, which in this work is understood from the conceptions and new definitions which appeared in Germany in the 60‟s and the 70‟s. These conceptions and definitions have been gaining much space among brasilian researchers, broadening their field of research regarding the discussion about the relation between historical knowledge and the practical life of men in society. The research conducted on historical consciousness was carried out based on the methodology of Historical Education, focusing the debate on the matter of the historical ideas of the students. The questionnaires applied to these students were inspired in the Project “Young Men In Face of History”, of Luis Fernando Cerri, who supplied to our research an important instrument for the debate about relations of EJA with historical knowledge. On the other hand, this research was possible only through na analysis of the economical and social context in which these youths and adults are in, allowing reflections driven by the historical experience of the participating subjects and the ties of this experience with the interpretations they make of and in history.